2019
DOI: 10.1590/0001-3765201920190149
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the wild tomato Solanum habrochaites to Phytophthora infestans is governed by a major gene and polygenes

Abstract: This work aimed to study the inheritance of resistance to Phytophthora infestans in tomato plants, using the maximum likelihood estimation function. The susceptible cultivar Santa Clara (Solanum lycopersicum) was used as the female genitor and the P. infestans resistant S. habrochaites f. glabratum accession (BgH 6902) as the male genitor. F 1 plants from the crossing were self-pollinated to produce F 2 progenies, and also backcrossed with P r and P S to produce BC 1:r and BC 1:S generations, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…In addition, the foliar oomycete Phytophthora infestans (Pinf) causes late blight disease in tomatoes. The wild tomato S. habrochaites shows resistance to Pinf, which is likely steered by polygenes [26]. Also in S. chilense Pinf resistance appears to be polygenic and of quantitative nature [53].…”
Section: Origin Of Wild Tomato Species and Their Resistotypesmentioning
confidence: 99%
“…In addition, the foliar oomycete Phytophthora infestans (Pinf) causes late blight disease in tomatoes. The wild tomato S. habrochaites shows resistance to Pinf, which is likely steered by polygenes [26]. Also in S. chilense Pinf resistance appears to be polygenic and of quantitative nature [53].…”
Section: Origin Of Wild Tomato Species and Their Resistotypesmentioning
confidence: 99%
“…Many resistance (R) genes identified from this species have been introgressed into the cultivated tomatoes ( Solanum lycopersicum ) (Chaudhary and Atamian, 2017). Novel disease resistance is continuously searched against diverse pathogens, including oomycete Phytophthora infestans (Li et al ., 2011; Nowakowska et al ., 2014; Copati et al ., 2019), fungi Botrytis cinerea (Finkers et al ., 2007) and bacteria Pseudomonas syringae (Bao et al ., 2015; Thapa et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the antimicrobial activity of 9H10epoZ does not seem to be specifically directed against tomato pathogens. Quantitative resistance to P. infestans was found in different accessions of S. habrochaites with quantitative trait loci (QTLs) located on chromosomes 11 and 5 (Johnson et al, 2012;Haggard et al, 2013Haggard et al, , 2014Copati et al, 2019). Accession LA2167 was not included in those studies, and it is still unknown whether the quantitative resistance identified there was based on specialized metabolites.…”
Section: From a Volatile Signalling Molecule To A Toxic Derivativementioning
confidence: 99%